A case report and literature review of myocardial infarction with nonobstructive coronary arteries (MINOCA) possibly due to acute coronary vasospasm induced by misoprostol - Hau, Nguyen Viet; Han, Luu Thi Kim; Minh, Le Huu Nhat; Kiet, Nguyen Anh; Phong, Tang Tuan; Duong, Nguyen Khanh; Yen, Phan Thi Hoang; Vinh, Nguyen Xuan; Hao, Nguyen Quan Nhu; Nguyen, Nguyen; Truyen, Thien Tan Tri Tai; Le, Nguyen Quoc Khanh (Frontiers in Cardiovascular Medicine, 2023)
Coronary artery vasospasm (CVS), an uncommon cause of acute chest pain, can be provoked by vasoconstriction-induced medications. Misoprostol, a prostaglandin analog, is a safe medication to terminate a pregnancy. However, misoprostol can cause coronary artery vasospasm due to vasoconstrictor properties, leading to acute myocardial infarction with nonobstructive coronary arteries (MINOCA), especially in patients with a high risk for cardiovascular disease. We report a case of a 42-year-old female with a past medical history of hypertension who presented with ST-elevation myocardial infarction following the administration of a high-dose Misoprostol. The fact that coronary angiogram and intravascular ultrasound revealed normal coronary arteries suggested transient coronary vasospasm. CVS is a severe but rare cardiac adverse effect associated with high-dose misoprostol. This medication should be prescribed with caution and close monitoring, especially in those with pre-existing heart disease or cardiovascular risk factors. Our case raises awareness of severe cardiovascular complications that can be related to using misoprostol in high-risk patients.